2018
DOI: 10.1111/jav.01659
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation and environmental correlates of apparent survival rates in adult tree swallows Tachycineta bicolor

Abstract: Determining demographic rates in wild animal populations and understanding why rates vary are important challenges in population ecology and conservation. Whereas reproductive success is reported frequently for many songbird species, there are relatively few corresponding estimates of annual survival for widespread populations of the same migratory species. We incorporated mark–recapture data into Cormack–Jolly–Seber models to estimate annual apparent survival and recapture rates of adult male and female tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…We were not able to determine comparable trends in nest box occupancy due to the short period of our study and for reasons associated with the changes in the number of nest boxes. Regional differences in recapture rates can be expected, although annual recapture rates at a site tend to be more consistent (Clark et al 2018). The mean return rate of banded adult females in our study was 21% across all years, which was within the range of 13% to 28% reported for Alberta and Saskatchewan, Canada (Houston and Houston 1987;Dunn and Hannon 1992).…”
Section: Discussionsupporting
confidence: 59%
“…We were not able to determine comparable trends in nest box occupancy due to the short period of our study and for reasons associated with the changes in the number of nest boxes. Regional differences in recapture rates can be expected, although annual recapture rates at a site tend to be more consistent (Clark et al 2018). The mean return rate of banded adult females in our study was 21% across all years, which was within the range of 13% to 28% reported for Alberta and Saskatchewan, Canada (Houston and Houston 1987;Dunn and Hannon 1992).…”
Section: Discussionsupporting
confidence: 59%
“…In SK, females that bred when ponds were abundant were able to make greater investments in reproduction, suggesting that aquatic insect food supply or quality can offset reproductive costs 32 , 63 . Although we were unable to directly assess links between pond abundance and survival because our measure of Relative Ponds was standardized to be independent of lifetime breeding attempts, higher apparent survival of females in years following higher pond abundance has been previously reported 64 . Thus, ponds are critically important for terrestrial species that rely on aquatic food resources, highlighting the urgent need to protect prairie wetland basins from further loss and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cliff swallows ( Petrochelidon pyrrhon o ta ), highest return rates were seen in individuals with intermediate baseline CORT levels, which could be due to stabilizing selection on CORT levels acting against the detrimental effects of very high or low CORT ( Brown et al, 2005 ; Bonier et al, 2009a ). Additionally, environmental variables ( Clark et al, 2018 ) or an individual's reproductive success may better predict return rates than baseline CORT: the positive (albeit non-significant) effect of fledgling number on maternal return rates that we detected suggests that females with higher reproductive success are more likely to return to a certain area to breed ( Bonier et al, 2009b ). Thus, CORT may affect return rates and survival indirectly, by affecting fledging success ( Shitikov et al, 2017 ; Weegman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 87%